Imprecise query processing in wireless sensor networks: a fuzzy-based approach. (2016) - Akhlaghi, Parand; Dehghan, Mehdi; Ebadzadeh, Mohammad Mehdi
Traditional query processing systems in sensor networks require precise and explicit definition of predicative thresholds to extract data. The acquired data can be imprecise and uncertain due to different reasons like measurement errors or environmental noise. In this paper, we take on a fuzzy-based approach to design a flexible query structure with linguistic and semantic predicates in sensor networks. In addition, we introduce a fuzzy-based query correlation index (FQCI), which quantifies the correlation between a sensor node and a query, based on a priori defined fuzzy membership functions, which are individual to each node. Also, our proposed fuzzy query structure can support queries with multiple predicates. This approach can reduce the rigidity in the declarative structure of query and minimise energy consumption, while providing a flexible service for event monitoring applications. Simulation results demonstrate that our method can achieve high fidelity with reasonable energy efficiency.